DESIGN OF THE DOBRA CHANTI SUSPENSION BRIDGE IN DISTRICT TEHRI GARHWAL, UTTARAKHAND, INDIA: Desain Jembatan Gantung Dobra Chanti di Distrik Tehri Garhwal, Uttarakhand, India - Hyun Tae Kang (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Since the Tehri dam was constructed on the River Bhagirathi in 2006, considerable productive land areas, many villages, including old Tehri town in Tehri-Garhwal district has been submerged. It has also disconnected the travel and transportation routes along the east slopes of the reservoir, making the local residents lose access to the New Tehri town, which is equipped with resident-friendly facilities including health and education institutions and markets. Accordingly, the Uttarakhand Government has proposed to build the Dobra-Chanti H.M.V. Suspension Bridge to meet the local demand for an easy intra-regional accessibility, especially between the left and right sides of the River Bhagirathi. The project consists of a single-span suspension bridge, an approach bridge at each end of the suspension bridge, and slope protection work on each side. The suspension bridge has a 440m-long stiffening truss girder, 57m-tall steel towers, locked coil cable systems including suspenders, and anchor blocks. The approach bridges are reinforced concrete bridges with T-shaped beams. And river side slopes installed on both banks are protected and stabilized through CC blocks, shotcrete, and anchor bolts. All cek dimension has met the requirement